Sintesis dan Karakterisasi Fe₂TiO₅ dari Besi Oksida dan Titanium Dioksida dengan Metode Planetary Ball-Mill: Synthesis and Characterization of Fe₂TiO₅ from Iron Oxide and Titanium Dioxide Using the Planetary Ball-Mill Method - Laode Kadir; M. H Azis; S. Musiam; V. A. Fabiani; Karnelasatri; D. Permana; T Azis; Syahrir (KOVALEN: Jurnal Riset Kimia, 2022)
The method of solid hydrogen storage through integration in metal hydride compounds is a new, promising method. This research has succeeded in synthesizing and characterizing the metal hydride alloy Fe-Ti system through a planetary ball-mill process. Based on the XRF analysis, it was found that the composition of Fe oxide content reached 56.22% while Ti oxide reached 43.78%. The FTIR study showed absorption at wavenumbers of 900 cm-1 and 500 cm-1. Both are typical absorptions for Ti-O and Fe-O groups, suggesting that the synthesized sample was successful. It can be seen from the XRD data that some of the diffractogram peaks of the resulting Fe-Ti compound match the peaks of the Fe2TiO5 and TiO2 compounds obtained from the Powder Diffraction File (PDF) database number 00-003-0374. After the refinement was performed, information was obtained that the synthesis of Fe-Ti alloy material using the planetary ball mill technique produced Fe2TiO5.